Adsorption Isotherms of Lactoflavine on Mint Adsorbent in Water Samples (Journal of the College of Basic Education, 2022)
This study is concerned with the removal of lactoflavin pigment from water through its adsorption by Iraqi Mint that found in Iraqi soils. The optimum conditions like PH, temperature, doses of adsorb ate and adsorbent and contact time, were studied by following the change in concentration of lactoflavin in solution on the basis of UV-visible spectroscopy method. It is found that time t=60 min, temperature=60 PH=9.0 and its initial concentration =30 ppm are the best conditions to get high efficiency of removal percent of lactoflavine by the Mint surface.The adsorption process has been found as endothermic in nature depending on thermodynamic parameters of Gibbs's free energy, change in entropy and enthalpy. The Langmiur and Fruendlich isotherms of lactoflavin adsorption on Iraqi Mint have studied in the 30-60 range, and it is found that the adsorption was endothermic heterogeneous processes.Keywords: Adsorption isotherms, lactoflavin, Mint as adsorbent.